Thermodynamics of primitive model electrolytes in the symmetric and modified Poisson-Boltzmann theories. A comparative study with Monte Carlo simulations - Quiñones, A.O.; Bhuiyan, L.B.; Outhwaite, C.W. (Condensed Matter Physics, 2018)
Osmotic coefficients, individual and mean activity coefficients of primitive model electrolyte solutions are computed at different molar concentrations using the symmetric Poisson-Boltzmann and modified Poisson-Boltzmann theories. The theoretical results are compared with an extensive series of Monte Carlo simulation data
obtained by Abbas et al. [Fluid Phase Equilib., 2007, 260, 233; J. Phys. Chem. B, 2009, 113, 5905]. The agreement between modified Poisson-Boltzmann predictions with the “exact” simulation results is almost quantitative for monovalent salts, while being semi-quantitative or better for higher and multivalent salts. The symmetric Poisson-Boltzmann results, on the other hand, are very good for monovalent systems but tend to deviate at
higher concentrations and/or for multi-valent systems. Some recent experimental values for activity coefficients
of HCl solution (individual and mean activities) and NaCl solution (mean activity only) have also been compared
with the symmetric and modified Poisson-Boltzmann theories, and with the Monte Carlo simulations. Обчислено осмотичнi коефiцiєнти, iндивiдуальнi та середнi коефiцiєнти активностi примiтивної моделi
розчинiв електролiтiв при рiзних молярних концентрацiях з використанням симетричної i модифiкованої
теорiй Пуассона-Больцмана. Теоретичнi результати порiвнюються з широким спектром даних симуляцiй
Монте Карло, отриманих Абасом та iн. [Fluid Phase Equilib., 2007, 260, 233; J. Phys. Chem. B, 2009, 113, 5905].
Узгодження мiж передбаченнями модифiкованої теорiї Пуассона-Больцмана та “точними” результатами
симуляцiй є майже кiлькiсним для моновалентних солей, будучи напiв-кiлькiсним чи кращим для бiльш
високих i багатовалентних солей. З iншого боку, результати симетричної теорiї Пуассона-Больцмана є
дуже добрими для моновалентних солей, але мають тенденцiю вiдхилятися при вищих концентрацiях
i/або для багатовалентних систем. Також здiйснено порiвняння деяких нещодавнiх експериментальних
значень для коефiцiєнтiв активностi розчинiв HCl (iндивiдуальних i середнiх активностей) i розчинiв NaCl
(тiльки середня активнiсть) iз симетричною та модифiкованою теорiями Пуассона-Больцмана, а також з
Монте Карло симуляцiями